(untitled) (Gaceta Técnica, 2023)
In this work, a program has been developed for the design of prequalified Simpson Strong-Tie Strong Frame type connections in accordance with the AISC regulatory requirements and within the prequalification and procedure limits contemplated in the ANSI/AISC 358-16 standard. To develop the program, was used the MATLAB software in its R2014a version, specifically its GUIDE environment for the design of the graphical interfaces and their respective programming. The program, called CONESTRONG (Simpson STRONG-Tie STRONG Frame Prequalified Connections), greatly facilitates the design of this type of connection, because it automatically verifies compliance with the various regulatory requirements and guides the user during the process with several suggestions. The results obtained with the program were compared with those of an example developed manually, with satisfactory results